Connections between Some Concepts of Polynomial Trichotomy for Noninvertible Evolution Operators in Banach Spaces - Mihai-Gabriel Babuţia; Nicolae Marian Seimeanu (International Journal of Differential Equations)
The present paper treats three concepts of nonuniform polynomial trichotomies for noninvertible evolution operators acting on Banach spaces. The connections between these concepts are established through numerous examples and counterexamples for systems defined on the Banach space of square-summable sequences.